Corporate social responsibility reporting and corporate reputation: an institutional and resource-based perspective / Suaini Othman - Othman, Suaini (Institute of Graduate Studies, UiTM, 2012)
transparency and in line with the prevailing Corporate Social Responsibility (CSR) reporting practices at the international level, the Malaysian regulatory authorities have made it mandatory for all public-listed companies to disclose their CSR activities in their annual reports beginning with the financial year ending 31 December 2007. The government believes that CSR reporting can be a potent tool for Malaysian companies to realise their enhanced reputation and in turn will assist them to compete effectively in the global market. Therefore, the objective of this study is to examine factors that influenced managements’ decisions on the quantity and quality of CSR disclosure during the unregulated (2005 and 2006) to the regulated (2007 and 2008) periods and whether these disclosures will have any effect on corporate reputation. The moderating and mediating effects in relation to CSR disclosures are also examined. Institutional Theory and Resource-based Perspective have been integrated to underpin this study. This study embarked upon a sequential mixed method approach, a combination of qualitative and quantitative investigations. The qualitative investigation involved faceto- face interviews with CSR managers while the quantitative investigation was based on content analysis of the annual reports of 248 companies listed on the main board of Bursa Malaysia over a period of four years, involving a total of 992 firm-year observations.